PENGARUH TINGKAT EKONOMI ORANG TUA TERHADAP MOTIVASI BERPRESTASI SERTA MINAT BELAJAR SISWA SD DI WILAYAH PERBATASAN KECAMATAN EMPANANG KAPUAS HULU - Lorensius Hendri; Eliana Yunitha Seran; Anna Marganingsih (STKIP Persada Khatulistiwa Sintang, 2020)
The background of this research is the economic level of parents, the majority of whom are farmers, which affects students' achievement motivation, and interest in learning. This is due to the lack of learning facilities, lack of support, and attention from parents that made students reluctant to study and to go to school. This research uses quantitative methods with the form of multiple correlations with simple correlation techniques. The population in this research was 32 people with a total sample of 32 people. In selecting the sample, the researcher applies a saturated nonprobability sampling technique. The data collection tools were a questionnaire sheet and documentation. In analyzing the data, the researcher used regression analysis, simple correlation analysis, and partial test. The results of the study prove 1) there is an effect of the level of the parents' economy on student achievement motivation, as evidenced by the value of tcount> ttable or 3,795> 2,042. 2) there is an effect of parents 'economic level on students' interest in learning, as evidenced by the value of tcount> ttable or 3.704> 2.042.